Multi-energy Complementary System for Joint Production of Liquid Fuel and Power. Issue 1 (November 2020) - Zhang, F; Zhu, L; Wu, P; Sun, L; Wang, Y
Abstract: By taking the energy complementation as an idea and the steam methane reforming as well as coal partial gasification and Fischer-Tropsch synthesis as the core technological means, this paper establishes a coal and methane to co-produce liquid fuels and power generation system using an ASPEN PLUS simulator, and realizes that the H2 /CO can be adjusted by directly changing the charging rate of raw materials with no need for additional equipment. At the same time, the coal char that has not yet been gasified is burned to provide the needed heat for the reaction of steam methane reforming, which can not only solve the demand of high heat of steam methane reforming, but also realize the gradient utilization of energy, thus reducing the loss in energy. In addition, some Fischer-Tropsch steam is used to generate power to further reduce the energy damage of the system. Two key parameters, namely coal input and Fischer-Tropsch recycle ratio, are discussed and their effects on system performances are analysed. At the optimum condition, the energy efficiency of this novel system reaches 52.5%, and the primary energy saving ratio reaches 30.4%.